First Synthesis of an Oridonin‐Conjugated Iridium(III) Complex for the Intracellular Tracking of NF‐κB in Living Cells. Issue 20 (21st March 2017) - Wang, Wanhe; Yang, Chao; Lin, Sheng; Vellaisamy, Kasipandi; Li, Guodong; Tan, Weihong; Leung, Chung‐Hang; Ma, Dik‐Lung
Abstract: NF‐κB is a critical transcription factor that plays an important role in mediating inflammation, the immune response, and cell proliferation. The activation of NF‐κB leads to an enhancement of proinflammatory mediator expression, which is implicated in the pathogenesis of a variety of diseases. Therefore, methods that allow the intracellular tracking of NF‐κB are particularly attractive because they can provide information regarding the pathways or stimulation responses that are involved in the activation of NF‐κB. In this work, we report a novel platform to track intracellular NF‐κB by employing the conjugated iridium(III) complex1, which was synthesized through the unique combination of a luminescent iridium(III) moiety with the natural product oridonin. Experiments conducted with p50 knockdown cells revealed that complex1 could detect the p50 subunit of NF‐κB in cellulo. Furthermore, complex1 tracked NF‐κB translocation induced by tumor necrosis factor‐α (TNF‐α) as a model stimulus, without affecting the translocation process itself. To the best of our knowledge, complex1 is the first metal‐based compound that has been reported to be capable of monitoring intracellular NF‐κB in living cells. Abstract : Tracking transcription factors : The first metal‐based compound that is capable of monitoring intracellular NF‐κB in living cells is reported. It was used as a probe to further understand the pathways or stimulation responses involved in NF‐κB activation.